Expressões da diversidade cultural na prática profissional dos assistentes sociais: o caso do CRAS de Parelheiros (SP) - Hurtado, Liliana Espinosa (2011)
The Social Work as a profession, historical-social turns in the same measure of the changes in society, reflect on their profissional practice, both in its permanence and its changes. This dissertation presents a case study where analysis was performed based on the perception of social workers on the expressions of cultural diversity in their professional practice as a field full of possibilities, challenges and breakthroughs, which are mediated by the diversity in its many manifestations that given new facets to the social question, the raw material of the profession. The fieldwork was carried out at Cras Parelheiros through interviews conducted with social workers who work at this location. In this rating and demonstrating the relevance of the topic for the profession, are seen the impact that has on professional practice contexts and subjects, as well as the struggles and work are intensified on the part of professionals to handle them. One proposal of this dissertation is to situate the interculturality as a form that it can be regarded as a valid possibility of intervention that contributes to professional practice in different contexts